Research competences with ICT in PhD students - Carlos Enrique George Reyes; Lilian Ivetthe Salado Rodríguez (Universidad de Guadalajara, 2019)
The research processes are part of the activities of PhD students; regardless of the focus of training or the educational modality of the program, the students will need to obtain, select, organize and analyze relevant information of various media, mainly Internet, as well as collaborate with their peers and socialize their findings in virtual media. The objective of this research is to analyze the research competences related to the use of ICT in PhD students from three Mexican universities. This is an exploratory and descriptive research with a mixed approach, it was used as a tool to retrieve information a questionnaire with Likert type scale items, multiple choice questions and open questions. The main findings identify that students frequently use technologies for communicative purposes and information search; however, they have areas of opportunity to determine the accuracy of the information they consult from the Internet, using digital tools to analysis the information in addition to participating in the dissemination of their knowledge using Internet platforms.